Evaluation of Lower Limb Arteriovenous Diameters in Indoor Soccer Athletes: Arterial Doppler Ultrasound Study - Mateus, Sónia; Paulo, Rui; Coelho, Patrícia; Rodrigues, Francisco; Marques, Vasco; Neiva, Henrique P.; Duarte-Mendes, Pedro (Frontiers in Physiology, 2021)
The purpose of this study was to analyze the arterial and venous diameters of lower limbs in indoor soccer athletes and non-athletes using Doppler ultrasound to identify the differences in the variation of arterial and venous diameters between groups. Additionally, we intended to verify the differences of arterial and venous diameters between the skilled member (right member) and the not skilled member in each group. 74 male volunteers, aged between 19 and 30 years old, were divided in a group of athletes (n = 37, 24 ± 2.7 years, soccer players from national championship), and a group of non-athletes (n = 37, 26 ± 2.83 years). Vascular lower limb was assessed using Doppler ultrasound (Philips HD7 echograph with linear transducer 7–12 MHz). The athletes showed higher diameters of right common femoral artery (p = 0.009; moderate), left common femoral artery (p = 0.005; moderate), right deep femoral artery (p = 0.013; moderate), right popliteal artery (p = 0.003; moderate), and left popliteal artery (p = 0.017; small) than non-athletes. Veins’ diameters were also higher in athletes, specifically the right deep femoral vein (p ≤ 0.001; large), left deep femoral vein (p ≤ 0.001; large), right popliteal vein (p ≤ 0.001; large), and left popliteal vein (p ≤ 0.001; large). Differences were found between the skilled and non-skilled leg in athletes in the popliteal vein (7.68 ± 1.44 mm vs. 7.22 ± 1.09 mm, respectively, p < 0.003). It seems that futsal athletes have superior mean diameters of lower limbs arteries and veins of the deep venous system to non-athletes. Moreover, the veins presented greater dilation, namely of the leg of the skilled lower limb.